Evaluate synthesized nanoparticles as a good inhibitor for lactobacillus acidophilus (Journal of the College of Basic Education, 2026)
Magnesium oxide nanoparticles (MgO NPs) exhibit promising antibacterial properties, making them a potential solution for combating bacterial infections linked to dental caries. This research concentrated on assessing the impacts of MgO NPs on Lactobacillus acidophilus, specifically assessing their antibacterial activity. The assessment the research included observing the impacts of MgO nanoparticles (NPs) on bacterial proliferation suppression. Proliferation inhibition was assessed by calculating the percentage decline in the cloudiness of the bacterial solution and the decrease in bacterial colony development subsequent to exposure to MgO NPs. The inquiry demonstrated a dosage-dependent, noteworthy (p < 0.05) impeding of growth and effects on Lactobacillus acidophilus when subjected to 10–100 μg/ml of MgO nanoparticles (NPs) across a 24-hour period. Fourier-transform infrared spectrometry (FTIR) analysis revealed that MgO NPs bond with polypeptides and glycogen in the microbial cell surface. Furthermore, Scanning electron microscopy (SEM) results emphasized the binding of MgO NPs to the cell wall, leading to its degradation and subsequent cellular damage. These findings confirm the bactericidal properties of MgO nanoparticles against Lactobacillus acidophilus.